ANALISIS EFEKTIVITAS DAN KONTRIBUSI PAJAK BAHAN BAKAR KENDARAAN BERMOTOR TERHADAP PENDAPATAN PAJAK DAERAH PADA BADAN PENDAPATAN DAERAH PROVINSI DKI JAKARTA - Seno Sudarmono Hadi (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2022)
The effectiveness and contribution of the Motor Vehicle Fuel Tax is one means that can measure how far the contribution of the Motor Vehicle Fuel Tax to Regional Tax Revenues is and also how far the level of achievement of tax collection by local governments regarding Motor Vehicle Fuel Tax is because regional tax revenues are very important. to build an area. This study aims to determine how big the contribution of Motor Vehicle Fuel Tax to Regional Tax Revenue of DKI Jakarta Province. And to determine how much effectiveness the Motor Vehicle Fuel Tax in DKI Jakarta Province is. This study is using a qualitative method. Based on the calculation of the effectiveness of Motor Vehicle Fuel Tax receipts for 2016-2020, it has increased but has decreased. The contribution of the Motor Vehicle Fuel Tax to Regional Tax Revenues for 2016-2020 is still lacking but the achievements each year have increased and decreased. From this explanation, the results of the Motor Vehicle Fuel Tax in 2016-2020 are very effective and still do not contribute to the regional tax revenue of DKI Jakarta Province.